A Voltage Improvement of Transmission System using Static Var Compensator via Matlab/Simulink - Siti Amely Jumaat; Ismail Musirin; Mazliya Mohd Baharun (Institute of Advanced Engineering and Science, 2017)
High demand in electricity consumption is rising and modern society would case to function without access to electricity. The volume of power transmitted and distributed are increasing, these need the requirements for high quality and reliable supply. At the same time, rising the costs and the growing environmental concerns make the process of develop a new power transmission line make complicated and the time consuming. One of alternatives to solve the issues is installed the Flexible AC Transmission System (FACTS). This research presents to modeling and simulation of Static Var Compensator (SVC) in the power system network using Matlab/Simulink Software. The objective function of this research is improvement the voltage of the system with four cases study for validation. From the simulation results shown that the SVC installation gives the effect to voltage of system.